Quantitative Trait Loci Analysis Based on High-Density Mapping of Single-Nucleotide Polymorphisms by Genotyping-by-Sequencing Against Pine Wilt Disease in Japanese Black Pine (Pinus thunbergii) - Hirao, Tomonori; Matsunaga, Koji; Shirasawa, Kenta (Frontiers in Plant Science, 2022)
Identifying genes/loci for resistance to pine wilt disease (PWD) caused by the pine wood nematode (PWN) is beneficial for improving resistance breeding in Pinus thunbergii, but to date, genetic information using molecular markers has been limited. Here, we constructed a high-density linkage map using genotyping-by-sequencing (GBS) and conducted quantitative trait loci (QTL) analysis for PWD resistance for the self-pollinated progeny of 'Namikata 73', which is the most resistant variety among resistant varieties of P. thunbergii, following inoculation tests with PWN. An S1 mapping population consisting of the 116 progenies derived from self-pollination of the resistant variety, ‘Namikata 73’ (resistance rank 5 to PWN, was inoculated with PWN isolate Ka-4 and evaluated for disease symptoms. To construct a high-density linkage map, we used single nucleotide polymorphisms (SNPs) identified by GBS based on next-generation sequencing technology and some anchor DNA markers, expressed sequence tag (EST)-derived SNP markers and EST-derived simple sequence repeat (SSR) markers, and genomic SSR markers. The linkage map had 13 linkage groups (LGs) consisting of 2,365 markers including 2,243 GBS-SNP markers over a total map distance of 1968.4 centimorgans (cM). Results from QTL analysis using phenotype data and the linkage map indicated that PWD resistance is controlled by a single locus located on LG-3, as identified in a previous study. This locus showed overdominant genetic action in the present study. With the confirmation of PWD1 in two different mapping populations (present study and a previous study), the locus associated with this region is thought to be a good target for marker-assisted selection in P. thunbergii breeding programs in order to obtain high levels of resistance to PWD caused by PWN.